Moving Beyond Postdevelopment: Facilitating Indigenous Alternatives for "Development" - Curry, George (Clark University, 2003)
Using the example of smallholder oil-palm production in Papua New Guinea, this article illustrates how elements of a market economy and modernity become enmeshed and partly transformed by local place-based nonmarket practices. The persistence, even efflorescence, of indigenous gift exchange, in tandem with greater participation in the market economy, challenges conventional notions about the structures and meanings of development. The introduced market economy can be inflected to serve indigenous sociocultural and economic goals by place-based processes that transform market relations and practices into nonmarket social relationships. These kinds of inflections of the market economy are common and widespread and therefore worthy of consideration for their theoretical insights into processes of social and economic change and the meanings of development. The article concludes by outlining some preliminary thoughts on how development practice could be modified to provide more scope for this process of inflection, so that development strategies accord better with indigenous sociocultural meanings of development.